Case Report: Clinical delineation of CACNA1D mutation: New cases and literature review - Alzahrani, Alshaimaa; Alshalan, Maha; Alfurayh, Mohammed; Bin Akrish, Abdulaziz; Alsubeeh, Najlaa A.; Al Mutairi, Fuad (Frontiers in Neurology, 2023)
Background Calcium ions are involved in several human cellular processes; nevertheless, the relationship between calcium channelopathies (CCs) and autism spectrum disorder (ASD) or intellectual disability (ID) has been previously investigated. We delineate the spectrum of clinical phenotypes and the symptoms associated with a syndrome caused by an inherited gain-of-function mutation in CACNA1D in a family with a history of neuropsychiatric disorders. We also review the clinical and molecular phenotype of previously reported variants of CACNA1D. Case presentation We report the case of a 9-year-old female patient, diagnosed with ASD, severe ID, hyperactivity, and aggressive impulsive behaviors. The father, who was a 65-year-old at the time of his death, had ID and developed major depressive disorder with catatonic features and nihilistic delusion, followed by rapidly progressive dementia. He died after experiencing prolonged seizures followed by post-cardiac arrest. The patient’s sister was a 30-year-old woman, known to have a severe ID with aggressive behaviors and sleep disorders. The sister has been diagnosed with bipolar disorder and psychosis. Through whole exome sequencing, a heterozygous previously identified and functionally characterized missense likely pathogenic variant was identified in the CACNA1D gene NM_001128840.3: c.2015C > T (p.Ser672Leu). These findings are consistent with the genetic diagnosis of autosomal dominant primary aldosteronism, seizures, and neurological abnormalities. This variant was found in the heterozygous status in the patient, her father, and her affected sister. Conclusion This case report will help to determine the key clinical features of this syndrome, which exhibits variable clinical presentations.